2014
DOI: 10.3109/01443615.2014.968114
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and chronic pain following different techniques of caesarean section: A comparative study

Abstract: Research examining long-term outcomes after childbirth performed with different techniques of caesarean section have been limited and do not provide information on morbidity and neuropathic pain. The study compares two groups of patients submitted to the 'Traditional' method using Pfannenstiel incision and patients submitted to the 'Misgav Ladach' method ≥ 5 years after the operation. We find better long-term postoperative results in the patients that were treated with the Misgav Ladach method compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Nevertheless, in these techniques, the skin incision was several centimeters higher (above the underwear or bikini level) than the original Pfannenstiel incision; moreover, it needs at least 15–17 cm in length ( 27 ), which means that these techniques’ abdominal incision looks wider than ours and much higher in level than the original Pfannenstiel incision. Joel–Cohen and Misgav–Ladach techniques did not meet the esthetic expectations of many women ( 28 ); however, Belci et al showed better long-term postoperative results (5 years after CS) in terms of the neuropathic and chronic pain and the cosmetic appearance of the scar in a comparative study ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in these techniques, the skin incision was several centimeters higher (above the underwear or bikini level) than the original Pfannenstiel incision; moreover, it needs at least 15–17 cm in length ( 27 ), which means that these techniques’ abdominal incision looks wider than ours and much higher in level than the original Pfannenstiel incision. Joel–Cohen and Misgav–Ladach techniques did not meet the esthetic expectations of many women ( 28 ); however, Belci et al showed better long-term postoperative results (5 years after CS) in terms of the neuropathic and chronic pain and the cosmetic appearance of the scar in a comparative study ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the Joel-Cohen/MML incision has lower rates of CPSP after CD compared with Pfannenstiel incision. 13,14 One hypothesis for lower incidence of pain with the Joel-Cohen incision has to do with the blunt dissection technique, which may lateralize the nerves without causing sharp transection or injury. Likewise, 1 randomized control trial has shown that the blunt dissection of fascia had a significantly lower rate of postsurgical pain and neuropathy 3 months after CD, compared with sharp dissection of the fascia.…”
Section: Incision Typesmentioning
confidence: 99%
“…Several studies have shown that the Joel-Cohen/MML incision has lower rates of CPSP after CD compared with Pfannenstiel incision 13,14. One hypothesis for lower incidence of pain with the Joel-Cohen incision has to do with the blunt dissection technique, which may lateralize the nerves without causing sharp transection or injury.…”
Section: Chronic Pain After Cesarean Delivery: Obstetrician's Viewmentioning
confidence: 99%
“…The results proved better outcome concerning pain, presence of neuropathic and chronic pain, and the satisfaction about the appearance of the scar. 22 If the technique is not standardized as suggested here, it will be very difficult to compare among surgeons and institutions. 1 Therefore, I suggest this method as a standardized universal method in China.…”
Section: Addendummentioning
confidence: 99%